2008
DOI: 10.1128/jb.01982-07
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibiotic Hypersensitivity among 4,000 Single-Gene-Knockout Mutants of Escherichia coli

Abstract: We have tested the entire Keio collection of close to 4,000 single-gene knockouts in Escherichia coli for increased susceptibility to one of seven different antibiotics (ciprofloxacin, rifampin, vancomycin, ampicillin, sulfamethoxazole, gentamicin, or metronidazole). We used high-throughput screening of several subinhibitory concentrations of each antibiotic and reduced more than 65,000 data points to a set of 140 strains that display significantly increased sensitivities to at least one of the antibiotics, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
196
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(217 citation statements)
references
References 62 publications
12
196
1
Order By: Relevance
“…Class 6 encompasses genes involved in protein synthesis/degradation and class 7 genes are of unknown function. Eighteen of the hypersensitive mutants we identified have also been shown to be sensitive to at least 1 of 22 clinically used antibiotics (16,17). These coding sequences most likely represent a common framework of genes crucial to resisting the adverse effects of toxic molecules (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Class 6 encompasses genes involved in protein synthesis/degradation and class 7 genes are of unknown function. Eighteen of the hypersensitive mutants we identified have also been shown to be sensitive to at least 1 of 22 clinically used antibiotics (16,17). These coding sequences most likely represent a common framework of genes crucial to resisting the adverse effects of toxic molecules (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we screened the entire Keio collection of approximately 4,000 E. coli single-gene knockouts (15) for mutants hypersensitive to bromoacetate. The Keio collection has previously been used to identify mutants hypersensitive to at least 1 of 22 different antibiotics (16,17). Similarly, screening of transposon libraries in Acinetobacter baylyi and P. aeruginosa has identified genes whose disruption hypersensitizes these organisms to a variety of antibiotics (18)(19)(20).…”
mentioning
confidence: 99%
“…Recent genetic screens in E. coli (Tamae et al, 2008) and P. aeruginosa (Breidenstein et al, 2008) have identified genes whose knockouts either reduce or increase sensitivity to ciprofloxacin, with .100 and 40 genes, respectively, contributing to resistance. Most of these mutations have not been genotyped in clinical samples, so that their contributions to clinical resistance cannot yet be fully determined.…”
Section: Parallel Evolution In Quinolone Resistancementioning
confidence: 99%
“…Concerning gut bacteria, these methods are mostly limited to the model gut bacteria Escherichia and Bacteroides spp. but have been valuable in understanding microbial interactions with drugs in vitro (Tamae et al, 2008) and in the host (García-González et al, 2017;Scott et al, 2017).…”
Section: Mastering Microbial Metabolismmentioning
confidence: 99%